VARIABILITY HOLES ON THE UPPER AND LOWER JAWS DEPENDING ON THE SKULL SHAPE - Дубровіна, Е.В.; Шерстюк, О.О.; Пронина, О.М.; Тарасенко, Я.А. (World of Medicine and Biology, 2016)
The presence of additional (Double) holes on the upper and lower jaws affect the quality of local anesthesia. Variability number, shape and location of doubling holes we found in 3 forms the skull, was 50% of the total and was not directly related to the anthropometric indices skull. However, the variation in the quantity and location dominates the brahitsefalicheskoho shape of the skull. Dual holes in 3 forms the upper jaw of the skull are more common (60% of cases) than in the mandible (40%). Their presence affects the topography of neurovascular bundle, expanding the zone of innervation of the bone and surrounding soft tissues.
Keywords: variability of holes; the holes of the upper and lower jaws; doubling holes local anesthesia